Novel concepts for designing semiconductor lasers. (October 2015) - Shchukin, V A; Ledentsov, N N; Maximov, M V; Gordeev, N Yu; Shernyakov, Yu M; Payusov, A S; Zhukov, A E
Abstract: We review novel concepts and demonstrate recent experimental data for edge- emitting semiconductor lasers with broad vertical waveguide. The ultimate case for waveguide extension in the vertical direction can be implemented by using the Tilted Wave Laser (TWL) approach. A TWL is composed of a thin active waveguide (typically 0.3-2 μm) optically coupled to a thick passive waveguide (10-150 μm). A TWL with a 26 μm-thick passive waveguide demonstrated low internal loss of 1.4 cm −1, maximum pulsed power 18 W and maximum CW power 4.7 W. Vertical far field of the TWL consists of two tilted narrow lobs of 2 degrees full width at half maximum each.